Multidisciplinary management of an unusual case of multiple developmental defects in lateral incisor followed by intrusive injury to primary incisors - Arpana V Bansal; Abhinav Bansal; Vinaya Kumar Kulkarni; Bosco Thomas; Reema Sharma Dhar (Wolters Kluwer Medknow Publications, 2012)
Dental traumatic injuries occur frequently in children. The close relationship between the apices of primary teeth and germ of the permanent successors can lead to developmental disturbances in the permanent dentition. Developmental disorder can occur in any tooth. One of the most common teeth affected is lateral incisor. These developmental anomalies can cause various clinical problems. Clinical and radiographic characteristics of these anomalies may sometime present confusing picture. Therefore, recognition of this condition, early diagnosis, and treatment are important to avoid complications. High prevalence of dental trauma in young children emphasizes the need of educational and preventive programs in schools. Dentist plays important role in early diagnosis of disturbances in the permanent successor teeth by rigorous clinical and radiographic follow-up examination.